Human alveolar macrophage response to Mycobacterium tuberculosis: immune characteristics underlying large inter-individual variability - Wolfgang Sadee; Ian H. Cheeseman; Audrey Papp; Maciej Pietrzak; Michal Seweryn; Xiaofei Zhou; Shili Lin; Amanda M. Williams; Mark D. Wewers; Heather M. Curry; Hao Zhang; Hong Cai; et al. (Communications Biology)
Abstract Mycobacterium tuberculosis (M.tb) infection infects human alveolar macrophages (HAMs). In freshly isolated HAMs from 28 healthy adults, we observe large inter-individual differences in bacterial uptake and growth, with tenfold variation in M.tb load by 72 h. While M.tb infection triggers expression changes of numerous host mRNAs, we examined which genes are most variably expressed (VE genes) between donors, as potential biomarkers of individual tuberculosis (TB) risk. The HAM RNA transcriptome following infection revealed thousands of differentially expressed (DE) genes and differential secretion of 25/27 proteins. Yet only 324 DE genes represent VE genes detected exclusively among DE genes in infected cells. Of 36 DE genes detected at all time points (2, 24, and 72 h), 14 are VE genes, indicating early emergence of the VE gene profile. 9/27 DE proteins following infection were encoded by VE genes. Systems analysis of VE RNAs identified a top-scoring network anchored by IL1B, involved in TB immune response. Independent M.tb-HAM transcriptome results from a TB-endemic region show significant overlap in DE genes, including VE genes identified in the main study. Thus, we identify a VE gene network activated upon M.tb-HAM infection with high inter-person variability, guiding studies on determining individual risk of M.tb infection and/or disease.